2022
DOI: 10.3390/oceans3030017
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Evaluation of Mono(2-ethylhexyl) Phthalate (MEHP) Detection in Common Bottlenose Dolphins (Tursiops truncatus) from Sarasota Bay, Florida, USA

Abstract: Phthalates are endocrine-disrupting chemicals added to plastics, personal care products, cleaning solutions, and pesticides. Extensive use has led to its exposure to wildlife, including common bottlenose dolphins (Tursiops truncatus) from Sarasota Bay, Florida, USA; however, there are gaps in knowledge regarding whether sample timing or geographic location influence exposure. Dolphins were evaluated for temporal and spatial variability in urinary mono(2-ethylhexyl) phthalate (MEHP) detection (2010–2019). Signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 95 publications
1
3
0
Order By: Relevance
“…Our findings align with previous studies where DEP and DEHP are the most common compounds found in cetacean species, independent of the matrix or area of study [30,31,70]. Moreover, studies assessing PAE metabolite concentrations have also detected DEP and DEHP metabolites in different cetacean species [31][32][33][34]36,37,71,72].…”
Section: Occurrence Of Paes In Delphinidssupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings align with previous studies where DEP and DEHP are the most common compounds found in cetacean species, independent of the matrix or area of study [30,31,70]. Moreover, studies assessing PAE metabolite concentrations have also detected DEP and DEHP metabolites in different cetacean species [31][32][33][34]36,37,71,72].…”
Section: Occurrence Of Paes In Delphinidssupporting
confidence: 91%
“…After a thorough review, we were only able to identify one study that has attempted to correlate phthalate exposure with physiological responses in cetaceans. In this study, Dziobak et al (2022) have described a positive relationship between blood thyroid hormone concentrations (free thyroxine) and urinary MEHP (mono(2-ethylhexyl) phthalate), a DEHP metabolite, for both adult female and male dolphins. They suggest that DEHP exposure may be impacting thyroid hormone homeostasis.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, the bioaccumulative and biomagnification potential of HMW phthalates (World Health Organization & International Programme on Chemical Safety, 1999;Beltifa et al, 2017) may mean top predators with large fat stores, such as pinnipeds, are exposed to phthalates through the food chain even without direct plastic ingestion. Most studies in marine species have investigated the concentration of phthalate metabolites (such as mono(2-ethylhexyl) phthalate (MEHP) and monoethyl phthalate (MEP)) in urine (Hart et al, 2020;Dziobak et al, 2021;Dziobak et al, 2022), which have been found in cetaceans (Fossi et al, 2012;Rian et al, 2020;Hart et al, 2020;Montoto-Martínez et al, 2021). However, recent studies have confirmed the presence of HMW phthalates (both parent compounds and their metabolites) in cetacean and polar bear blubber (Baini et al, 2017;Routti et al, 2021), including BBzP and its major metabolites (Baini et al, 2017).…”
Section: Introductionmentioning
confidence: 99%